FOOD ADULTERATION AND ITS FORENSIC QUANTIFICATION USING STABLE ISOTOPE ANALYSIS: A REVIEW (Journal of Forensic Medicine & Toxicology, 2021)
Adulterations and mislabellings of food items has reached at its draconian levels worldwide thesedays due to rapidly increasing fraudulent practices. Addition of unwanted substances deteriorate the authenticity, natural composition and quality of edible food substances leading to certain harmful effects and chronic diseases like stomach disorders, anaemia, brain damages, paralysis and even cancers. Forensic quantification of these adulterants using latest scientific armamentarium becomes essential to safeguard the interests of the consumers. Stable isotope analysis has been applied to newer situations to extract maximum societal benefits of latest technological advancements (Ehleringer et al, 2015). Stable isotope analysis has proved an important tool for detection of food adulterants, thus helping the investigating agencies to take actions against dishonest traders and suppliers, and sometimes producers who play with the health and wellness of the masses. Honey, sugars, beverages, dairy products, cereals, coffee etc., are the commonly adulterated or mislabelled food products in India and the isotopic analysis has been scantly used for detecting adulterations in food items. Present review article gives a brief account of food adulteration and the role of stable isotope analyses in detecting and quantifying such adulterants in different food items.
Keywords: Food adulteration; quality and authenticity; quantification; stable isotope analysis; India